Uropathogenic Escherichia coli modulates immune responses and its curli fimbriae interact with the antimicrobial peptide LL-37. - Ylva Kai-Larsen; Petra Lüthje; Milan Chromek; Verena Peters; Xiaoda Wang; Asa Holm; Lavinia Kádas; Kjell-Olof Hedlund; Jan Johansson; Matthew R Chapman; Stefan H Jacobson; Ute Römling; et al. (PLoS Pathogens)
Bacterial growth in multicellular communities, or biofilms, offers many potential advantages over single-cell growth, including resistance to antimicrobial factors. Here we describe the interaction between the biofilm-promoting components curli fimbriae and cellulose of uropathogenic E. coli and the endogenous antimicrobial defense in the urinary tract. We also demonstrate the impact of this interplay on the pathogenesis of urinary tract infections. Our results suggest that curli and cellulose exhibit differential and complementary functions. Both of these biofilm components were expressed by a high proportion of clinical E. coli isolates. Curli promoted adherence to epithelial cells and resistance against the human antimicrobial peptide LL-37, but also increased the induction of the proinflammatory cytokine IL-8. Cellulose production, on the other hand, reduced immune induction and hence delayed bacterial elimination from the kidneys. Interestingly, LL-37 inhibited curli formation by preventing the polymerization of the major curli subunit, CsgA. Thus, even relatively low concentrations of LL-37 inhibited curli-mediated biofilm formation in vitro. Taken together, our data demonstrate that biofilm components are involved in the pathogenesis of urinary tract infections by E. coli and can be a target of local immune defense mechanisms.